2020
DOI: 10.1111/jofi.12966
|View full text |Cite
|
Sign up to set email alerts
|

Local Crowding‐Out in China

Abstract: In China, between 2006 and 2013, local public debt crowded out the investment of private firms by tightening their funding constraints while leaving state-owned firms' investment unaffected. We establish this result using a purpose-built data set for Chinese local public debt. Private firms invest less in cities with more public debt, with the reduction in investment larger for firms located farther from banks in other cities or more dependent on external funding. Moreover, in cities where public debt is high,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(117 citation statements)
references
References 80 publications
(114 reference statements)
3
113
0
1
Order By: Relevance
“…7 These actions were reinforced by the State Council in its 2013 Guidelines. 8 In the introduction, we term this quality-control regulation the safe-loan regulation. This regulation gave banks incentives to invest in risky nonloan assets that deliver higher expected returns.…”
Section: Instruments For Monetarymentioning
confidence: 99%
See 2 more Smart Citations
“…7 These actions were reinforced by the State Council in its 2013 Guidelines. 8 In the introduction, we term this quality-control regulation the safe-loan regulation. This regulation gave banks incentives to invest in risky nonloan assets that deliver higher expected returns.…”
Section: Instruments For Monetarymentioning
confidence: 99%
“…subject to equations (7), (8), (9), and 10, where β is a subjective discount factor and E m represents the mathematical expectation with respect to monetary policy shocks. The solution to the bank's optimization is fully derived in online Appendix B.…”
Section: A a Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The results conclude that there is a positive relationship between government expenditure and interest rate, which abides with the result from this study such that an increase in public expenditure will raise the interest rate. Yi Huang (2017) analyzed the crowding out effect of public debt on private-owned companies in China using the dataset for Chinese local public debt. The results suggested that there is a negative relationship between city-level public debt and private investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the perspective of the economic institutions, it can figure out the institutional factors of the credit allocation differences between S.O.E.s and P.E.s and helps to eliminate the mismatch problem. With the background of China's economic institutions, the finance sector is not a completely independent market entity and its credit allocation along with strong government preference (Huang et al, 2020). Government intervention and ownership relationship affect the credit allocation in the finance sector.…”
Section: Introductionmentioning
confidence: 99%